Evaluation on the effects ofdifferent plant matter in water on Aedes aegypti development (Diptera: Culicidae) - Mahmud Shah, Nur lyana; Che Dom, Nazri; Abdullah, Samsuri; Precha, Nopadol; Dapari, Rahmat (Springer, 2022)
Knowledge on the factors associated with the development of Aedes aegypti (Linnaeus) can provide a better understanding of vector surveillance and encourage prevention practices for Aedes control strategy. The purpose of this research was to study the effect of different plant materials contained in the water in artificial container towards the development of Ae. aegypti. This is an experimental research that involve triplication of artificial containers each filled with a total of 30 eggs exposed to different plant materials (twig, dry grasses and dry leaves) at different concentration (i.e., 1.7 g/l, 2.5 g/l and 3.3 g/l) respectively. Observation on the development day, number or larvae at each fourth instar, and pupation period were monitored daily until adult emergence under controlled environment in insectarium. The experiment indicated that the time period required for the development of larvae was positively influenced by the presence of plant materials found in water for a conducive larval growth environment. This study revealed that the presence of plant materials contained in the water of breeding habitat support the development of Ae. aegypti larvae until its adult emergence. In conclusion, organic matters present in plant materials were identified as responsible factors in response to the development time of Ae. aegypti larvae during their aquatic stage.